Comparison of efficiency of intravitreal ceftazidime and intravitreal cefepime in the treatment of experimental Pseudomonas aeruginosa endophthalmitis - Deniz, Nurettin; Aydemir, Orhan; Guler, Mete; Akpolat, Nusret; Kizirgil, Ahmet (Wolters Kluwer Medknow Publications, 2013)
In this study, we evaluated the efficiency of cefepime in the treatment of experimental Pseudomonas aeruginosa endophthalmitis. We compared the findings with the standard dose of ceftazidime (1 mg/0.1 ml). Thirty-six New-Zealand White rabbits were divided into 6 equal groups and were treated with different methods (Group 1 = sham, Group 2 = 0.5 mg/0.1 ml cefepime, Group 3 = 1 mg/0.1 ml cefepime, Group 4 = 2 mg/0.1 ml cefepime, Group 5 = 1 mg/0.1 ml ceftazidime, Group 6 = control). The eyes of rabbits in each group were examined clinically on 1st, 3rd, and 6th day of the experiment. At 6th day, 0.1 ml vitreous humor aspirates were obtained and plated for quantification on the blood agar and the results were expressed as colony-forming unit/ml. Subsequently, the eyeballs were enucleated and the histopathological evaluation was performed. Our findings denoted beneficial effects of cefepime in treatment groups (especially, in Groups 3 and 4). Intravitreal cefepime may be an alternative drug in the treatment of P. aeruginosa endophthalmitis.
Keywords: Cefepime; ceftazidime; endophthalmitis; Pseudomonas aeruginosa